2011
DOI: 10.1080/10590501.2011.629974
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic Aromatic Hydrocarbons and Digestive Tract Cancers: A Perspective

Abstract: Cancers of the colon are most common in the Western world. In majority of these cases, there is no familial history and sporadic gene damage seems to play an important role in the development of tumors in the colon. Studies have shown that environmental factors, especially diet, play an important role in susceptibility to GI tract cancers. Consequently, environmental chemicals that contaminate food or diet during its preparation becomes important in the development of GI cancers. Polycyclic aromatic hydrocarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(117 citation statements)
references
References 184 publications
(180 reference statements)
2
113
0
2
Order By: Relevance
“…Moreover, the consumption of red and processed meat has been found to be associated with other epithelial-deriving neoplasms, and this evidence is supported by the results of the aforementioned study by Romaguera et al [16]. There are also mechanistic data that support this hypothesis: Red meats feature many compounds that are known to induce DNA mutation such as heme iron, heterocyclic amines and polycyclic aromatic hydrocarbons [34][35][36]. A direct correlation between refined cereals has been found to be associated with an increased risk of BE, EAC and cancer in general [37,38].…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, the consumption of red and processed meat has been found to be associated with other epithelial-deriving neoplasms, and this evidence is supported by the results of the aforementioned study by Romaguera et al [16]. There are also mechanistic data that support this hypothesis: Red meats feature many compounds that are known to induce DNA mutation such as heme iron, heterocyclic amines and polycyclic aromatic hydrocarbons [34][35][36]. A direct correlation between refined cereals has been found to be associated with an increased risk of BE, EAC and cancer in general [37,38].…”
Section: Discussionsupporting
confidence: 58%
“…The antimutagenicity was highlighted against 2AA, which represents one of the main carcinogenic health hazards associated to occupational exposure and dietary intake, being frequently formed at high temperatures during cooking and frying of meat and fish, or during the incomplete combustion of organic compounds (Diggs et al, 2011). Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Even at low levels long term exposure to some PAHs viz., pyrene and BaP has been identified as the cause of cancer in laboratory animals (Diggs et al, 2011). Toxic kinetics study on animal has also shown adverse reproductive and developmental effects from PAHs exposure as such effects have not usually been detected in humans (Wells et al, 2010).…”
Section: Acute or Short-term Health Effects:-mentioning
confidence: 99%